Exploring the Root Canal Morphology of Third Molars in the Bosnia and Herzegovina Population - Aida Džanković; Amra Mahmutović; Samra Korać; Irmina Tahmiščija; Alma Konjhodžić; Lajla Hasić-Branković; Naida Hadžiabdić (University of Zagreb. School of Dental Medicine, 2024)
The objective of this study was to evaluate the root canal morphology of third molars in the BosniaHerzegovina population. Materials and methods: A total of 241 extracted third molars (105 maxillary and 136 mandibular) were subjected to a clearing procedure. The specimens were categorized into ten groups based on the Alavi classification for maxillary third molars (MaxTMs), and six groups were based on the Gulabivala classification for mandibular third molars (ManTMs). Root canal type according to the Vertucci classification, the presence and position of lateral canals, and intercanal communication were analyzed using a stereomicroscope x15. Results: MaxTMs had three roots in 77.13% of the samples. Among MaxTMs, the most common morphology was three fused roots (33.33%) and Vertucci's type VIII (54. 28% of samples in Alavi's Group IV). 60.29% of ManTMs have two separate roots (Gulabivala's Groups II and III). The most prevalent types in mesial roots were type I (41.46% in Group II) and type IV (48.78% in Group III), although type I predominated in distal roots (91.24% and 100% in Groups II and III, respectively). Conclusion: Single-rooted third molars usually have a root canal morphology that is more favorable for endodontic treatment. In contrast, third molars with fused roots often have more complex root canal morphology.